Proteins exported via the PrsD-PrsE type I secretion system and the acidic exopolysaccharide are involved in biofilm formation by Rhizobium leguminosarum - Russo, Daniela Marta (2006)
The type I protein secretion system of Rhizobium leguminosarum bv. viciae encoded by the prsD and prsE genes is responsible for secretion of the exopolysaccharide (EPS)-glycanases PlyA and PlyB. The formation of a ring of biofilm on the surface of the glass in shaken cultures by both the prsD and prsE secretion mutants was greatly affected. Confocal laser scanning microscopy analysis of green-fluorescent-protein-labeled bacteria showed that during growth in minimal medium, R. leguminosarum wild type developed microcolonies, which progress to a characteristic three-dimensional biofilm structure. However, the prsD and prsE secretion mutants were able to form only an immature biofilm structure. A mutant disrupted in the EPS-glycanase plyB gene showed altered timing of biofilm formation, and its structure was atypical. A mutation in an essential gene for EPS synthesis (pssA) or deletion of several other pss genes involved in EPS synthesis completely abolished the ability of R. leguminosarum to develop a biofilm. Extracellular complementation studies of mixed bacterial cultures confirmed the role of the EPS and the modulation of the biofilm structure by the PrsD-PrsE secreted proteins. Protein analysis identified several additional proteins secreted by the PrsD-PrsE secretion system, and N-terminal sequencing revealed peptides homologous to the N termini of proteins from the Rap family (Rhizobium adhering proteins), which could have roles in cellular adhesion in R. leguminosarum. We propose a model for R. leguminosarum in which synthesis of the EPS leads the formation of a biofilm and several PrsD-PrsE secreted proteins are involved in different aspects of biofilm maturation, such as modulation of the EPS length or mediating attachment between bacteria